Fractionation of silver isotopes in native silver explained by redox reactions. (1st March 2018) - Mathur, Ryan; Arribas, Antonio; Megaw, Peter; Wilson, Marc; Stroup, Steven; Meyer-Arrivillaga, Danilo; Arribas, Isabel
Abstract: Scant data exist on the silver isotope composition of native silver specimens because of the relative newness of the technique. This study increases the published dataset by an order of magnitude and presents 80 silver new isotope analyses from native silver originating from a diverse set of worldwide deposits (8 deposit types, 33 mining districts in five continents). The measured isotopic range (defined as δ 109 Ag/ 107 Ag in per mil units compared to NIST 978 Ag isotope standard) is +2.1 to −0.86‰ (2σ errors less than 0.015); with no apparent systematic correlations to date with deposit type or even within districts. Importantly, the data centering on 0‰ all come from high temperature hypogene/primary deposits whereas flanking and overlapping data represent secondary supergene deposits. To investigate the causes for the more fractionated values, several laboratory experiments involving oxidation of silver from natural specimens of Ag-rich sulfides and precipitation and adsorption of silver onto reagent grade MnO2 and FeOOH were conducted. Simple leach experiments demonstrate little Ag isotope fractionation occurred through oxidation of Ag from native Ag (Δsolution-native 109 Ag = 0.12‰). In contrast, significant fractionation occurred through precipitation of native Ag onto MnO2 (up to Δsolution-MnO2 109 Ag = 0.68‰, or 0.3amu). Adsorption of silver onto the MnO2 and FeOOH did not produce as large fractionation as precipitation (mean value of Δsolution-MnO2 109 Ag = 0.10‰). The most likely cause for the isotopic variations seen relates to redox effects such as the reduction of silver from Ag (I) to Ag° that occurs during precipitation onto the mineral surface. Since many Ag deposits have halos dominated by MnO2 and FeOOH phases, potential may exist for the silver isotope composition of ores and surrounding geochemical haloes to be used to better understand ore genesis and potential exploration applications. Aside from the Mn oxides, surface fluid silver isotope compositions might provide information about geochemical reactions relevant to both environmental and hydrometallurgical applications.